PREFERENSI PROFESI YANG DIMINATI OLEH SISWA SD DI LINGKUNGAN MASYARAKAT PETANI DI KABUPATEN SLEMAN - Rachmadhani, Sherly; Kurniawan, Muhammad Ragil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the career choices of elementary school students in the agricultural area of ​​Prambanan District, Sleman Regency, and their relationship with the condition of agricultural land, family origin, and students' views on the farming profession. The method used is a Mixed Method with an Explanatory Sequential model, with quantitative data in the form of a questionnaire regarding students' career choices and secondary data about the area, and qualitative data obtained through interviews with five students. The results obtained show that although Prambanan District has 33.67% of the total agricultural land area, only about 12% of the population works in agriculture, while the background of students' parents' work is mostly from the non-agricultural sector. Students' career choices tend towards digital professions such as TikTokers and YouTuber, while the farming profession ranks lowest. Qualitative findings indicate that students are aware of the important role of the farming profession in meeting food needs, but consider it a difficult job and not in line with their aspirations. Interest in the farming profession arises under certain conditions, particularly when supported by modern agricultural technology. Therefore, improving agricultural-related career literacy from the elementary level is crucial to supporting the sustainability of the food sector in the future.